Faktor-Faktor Yang Mempengaruhi Curahan Kerja Petani Kentang Di Kecamatan Karangreja Kabupaten Purbalingga - Aulia Shabila, Riany (GEMA EKONOMI, 2023)
Karangreja District, Purbalingga Regency is one of the potato producing areas in Central Java. Potato production in the area does not always rise and even tends to fluctuate. This happens because of several production factors, namely land area, pesticides, fertilizers and labor. The area of land planted with potatoes in Karangreja District remains every year. The amount and type of pesticides and fertilizers are also the same every year because farmers use fertilizers and pesticides according to the partner company's Standard Operating Procedures (SOP). So that labor becomes a factor of production that needs further research. The purpose of this study is to determine 1) The amount of work of potato farmers in Kutabawa Village, Karangreja District, Purbalingga Regency, 2) Factors that affect the outpouring of work of potato farmers in Kutabawa Village. The research method is carried out with a quantitative descriptive approach. The sampling technique uses simple random sampling. The number of samples was 70 potato farmers in Karangreja District. Data collection techniques in the form of questionnaires, observations and document studies. Data analysis using uptime outpouring and multiple linear regression. The results showed that 1) The total outpouring of work of potato farmers in Karangreja District, Purbalingga Regency amounted to 2,225.93 HOK per planting season, 2) Factors that affect the outpouring of work of potato farmers are land area, farming experience and the number of family dependents.